Pediatric Hand Injuries. Issue 3 (July 2016) - Sullivan, Matthew A.; Cogan, Charles J.; Adkinson, Joshua M.
Abstract : Pediatric hand injuries are extremely common. Although many hand injuries are adequately managed in the emergency department, some may need evaluation and treatment by a pediatric hand surgeon to ensure a good functional outcome. This article discusses the diagnosis and management of the most common pediatric hand maladies: fingertip injuries/amputation, tendon injuries, and phalangeal and metacarpal fractures. The plastic surgery nurse should be familiar with hand injuries that require intervention to facilitate efficient management and optimal postoperative care.